Oxide and Nitride Semiconductors Processing, Properties, and Applications - Yao, Takafumi; Hong, Soon-Ku.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This is a unique book devoted to the important class of both oxide and nitride semiconductors. It covers processing, properties and applications of ZnO and GaN. The aim of this book is to provide the fundamental and technological issues for both ZnO and GaN. Materials properties, bulk growth, thin and thick films growth, control of polarity and application, nonpolar growth, structural defects, optical properties, electrical properties, nanostructures and the applications, and light emitters based on GaN and ZnO are treated succinctly. The unique format of touching both materials in each chapter enables this book to be very fresh, essential, and easy-to-access for readers who have interests in, and need getting more involved with, the most exciting compound semiconductors, ZnO and GaN.
Basic Properties of ZnO, GaN, and Related Materials -- Solvothermal Growth of ZnO and GaN -- Growth of ZnO and GaN Films -- Control of Polarity and Application to Devices -- Growth of Nonpolar GaN and ZnO Films -- Structural Defects in GaN and ZnO -- Optical Properties of GaN and ZnO -- Electrical Properties of GaN and ZnO -- GaN and ZnO Light Emitters -- ZnO and GaN Nanostructures and their Applications.
Keywords: Materials science; Solid state physics; Optics; Optoelectronics; Plasmons (Physics).; Spectroscopy; Microscopy; Engineering; Optical materials; Electronic materials; Materials Science; Optical and Electronic Materials; Solid State Physics; Spectroscopy and Microscopy; Optics, Optoelectronics, Plasmonics and Optical Devices; Engineering, general; Electronic books